GC-MS ANALYSIS, QUALITATIVE AND QUANTITATIVE PHYTOCHEMICAL COMPOSITION OF Boerhavia diffusa (Linn.) LEAF EXTRACT CHARACTERIZING ITS MEDICINAL USE - Oseni, T. E.; Adejoh, M. E.; Omowaye, Olaniyi Stephen; Attah, F.; Peter, J.; Tennyson, M. A.; Oladipe, T. T.; Olubiyo, C. K.; Oludare, T. T.; Odiba, J. C.; Ocean, H. O.; Olopade, T. T. (FUDMA Journal of Sciences, 2024)
Boerhavia diffusa Linn., commonly known as punarnava, is a perennial herb of the Nyctaginaceae family, renowned for its medicinal significance in traditional medicine, particularly in India. The leaves of Boerhavia diffusa were extracted using a Soxhlet extractor, and the resulting ethanolic extract was subjected to qualitative and quantitative phytochemical analysis. Qualitative screening revealed the presence of phenols, tannins, alkaloids, saponins, flavonoids, terpenoids, steroids, and cardiac glycosides. Quantitative analysis demonstrated significant concentrations of phenols (344.97 mg/100g), flavonoids (67.72 mg/100g), and tannins (84.33 mg/100g). Advance GC-MS profiling identified 16 bioactive compounds, including benzofuran, stigmasterol, pentadecanoic acid, and phytol, which exhibit diverse pharmacological activities such as antioxidant, anti-inflammatory, and antimicrobial effects. The study highlights the potential of Boerhavia diffusa as a source of novel therapeutic agents, bridging traditional knowledge with modern scientific techniques. Further research is recommended to explore the synergistic effects, pharmacokinetics, and bioavailability of its phytochemicals to validate its clinical applications. This investigation substantiates the medicinal value of Boerhavia diffusa and advocates for its integration into contemporary medicine, offering a promising avenue for the advancement of herbal medicine.
Keywords: Boerhavia diffusa; GC-MS analysis; Qualitative; Quantitative; Phytochemical